Efeito alelopático de espécies exóticas invasoras sobre espécies nativas de floresta estacional semidecidual - Ribeiro, Vandjore de Mattos (2015)
Invasive alien species can interfere with the development of native species for the production and release of chemicals in the environment, a phenomenon known as allelopathy. Thus, the aim of this study was to investigate the allelopathic potential and oxidative stress on seeds and Cucumis sativus seedlings when submitted to aqueous extracts of Leucaena leucocephala. Therefore, we evaluated the germination behavior, early growth and activity of antioxidant enzymes in different soaking time of seeds and target species of seedlings. The results indicated that there was interference from L. leucocephala extracts on the germination of variables, speed index and average germination time, decreased length of root and shoot growth stimulus. Regarding enzymatic activity, it was found high activity of catalase enzyme after 24 hours of soaking seeds, and low activity in the seedlings after 168 hours of soaking. As for the peroxidase enzyme, there was low activity in seeds and high activity in the C. sativus seedlings. They were also investigated the effect of aqueous extracts in the laboratory and powdered extracts, in a greenhouse, Leucaena leucocephala and Hovenia dulcis on the germination and early development of native species Mimosa bimucronata and Peltophorum dubium. Both extracts revealed allelopathic potential on seed germination and initial growth of M. bimucronata. No negative interference of extracts from the donor species on the germination of P. dubium, however, seedlings subjected to L. leucocephala extract had interference in the initial development, and the elongation of the radicle more sensitive to the effects of the extracts. Regarding the effects of the extract powder on the development of the species, it was found that there was no interference in the growth variables for the species M. bimucronata, however, to P. dubium, extracts promoted difference in the height of the seedlings field conditions. According to the methodology used and the results obtained, it observed that the allelopathic effects observed in the laboratory were more significant, suggesting that in a controlled environment, with little variation of environmental factors, the action of allelochemicals interfere more actively on seed germination and seedling development of the recipient species.